Thermal behavior of the Klein Gordon oscillator in a dynamical noncommutative space - Ilyas Haouam (Scientific Reports)
Abstract We investigate the thermal properties of the Klein–Gordon oscillator in a dynamical noncommutative space. These properties are determined via the partition function, which is derived using the Euler–Maclaurin formula. Analytical expressions for the partition function, free energy, internal energy, entropy, and specific heat capacity of the deformed system are obtained and numerically evaluated. The distinct roles of dynamical and flat noncommutative spaces in modulating these properties are rigorously examined and compared. Furthermore, visual representations are provided to illustrate the influence of the deformations on the system’s thermal behavior. The findings highlight significant deviations in thermal behavior induced by noncommutativity, underscoring its profound physical implications.